GAMBARAN KARAKTERISTIK AKSEPTOR KB PASCA SALIN DENGAN METODE IMPLANT DI PUSKESMAS NGADIREJO TEMANGGUNG JAWA TENGAH - SULASTRI, ANI (Universitas Muhammadiyah Surabaya, 2023)
Objective: The government is pursuing strategic programs to reduce MMR, unmeet need and TFR with postpartum family planning. The purpose of this study was to find out how the characteristics of postnatal family planning acceptors with the implant method are described.Methods: This study uses a quantitative descriptive method. The population in this study were 36 respondents who received postnatal family planning implants using a total sampling technique. The type of data uses K/IV/KB/15 secondary data. Data analysis used univariate analysis with frequency distribution.Results: The results showed that the description of the characteristics of postnatal contraception acceptors using the implant method was in healthy reproductive age of 20-35 years (75%), middle/high school secondary education (72.2%), number of children â‰¥3 (50%), history of contraception. have ever had family planning (55.6%), have health insurance/JKN (83.3%) and the characteristics of working and not working obtained the same number (50%).Conclusion: The description of postnatal contraception acceptor characteristics with implant method at Ngadirejo Primary Health Center Temanggung Central Java was the majority in healthy reproductive age (20-35 years), secondary education (Junior High School/Senior High Scholl), a history of contraception that has had family planning, and has Health Insurance/JKN. The characteristics of the number of children, working and not working are obtained in the same number.